Stock Liquidity and Default Risk among Listed Firms in Kenya - Sikuku, Emmanuel Wanjala; Koske, Naomi Chepkorir; Bonuke, Ronald; Githaiga, Nderitu (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
Default risk is costly for investors and firms, particularly in less developed financial markets such as Kenya. Default risk may even lead to the collapse of an entire financial system. Therefore, this study sought to examine the effect of stock liquidity on default risk among listed firms in the Kenya equity market. The study used a sample of 31 nonfinancial firms listed in the Nairobi Securities Exchange between 2011 and 2020. Data was analyzed using fixed and random effect panel data estimation techniques. The findings of this study demonstrate a significant negative relationship between the stock liquidity and default risk of listed firms in Kenya. Based on the results, this study recommends that stock market regulators and policymakers pay special attention to promoting/maintaining stock market liquidity as a way of cushioning listed firms from falling into default risk.